Comparing Cementing Techniques in Total Knee Arthroplasty: An In Vitro Study - Wetzels, Thomas; van Erp, Joost; Brouwer, Reinoud W.; Bulstra, Sjoerd K.; van Raay, Jos J. A. M. (The Journal of Knee Surgery, 2019)
Aseptic loosening remains to be a major reason for revision in total knee arthroplasty. Cement penetration of 2 to 5 mm increases the interface strength and consequently decreases the likelihood of loosening. But despite this overall accepted optimal cement penetration, there is still a wide variety of cementing techniques used in total knee arthroplasty. The purpose of this study was to evaluate two cementing techniques on the tibial and femoral sides, with regard to cement penetration. Five paired cadaveric knees were used. A total knee arthroplasty was placed according to standard practice, with a setup that mimics the clinical practice. On the tibial side, we compared the application of cement to the bone surface alone, to the application of cement to both the bone surface and the component. On the femoral side, we compared the application of cement to the posterior condyles of the component and to the anterior and distal parts of the bone surface, to the application of cement to the component alone. After the cement had cured, the arthroplasty was removed and the bone was examined to determine the cement penetration using digital software. When applying cement to both the tibial bone surface and the tibial component, the cement penetration increased compared with applying cement to the tibial bone surface alone (3.46 vs. 2.66 mm, p = 0.007). With regard to the distal femoral cuts, the cement penetration did not vary when applied to either the bone or the component (2.81 vs. 2.91 mm). But applying it to the anterior bone surface did seem preferable, when compared with only applying it to the component. The average cement penetration did not differ, but applying the cement to the bone did enlarge the total length of the cement distribution (2.48 vs. 0.96 mm, p = 0.011). Almost no cement was detected on the posterior surface of the femoral cut. We concluded that applying cement to both the tibial bone surface and the component improves cement penetration.
Keywords: total knee arthroplasty; cement; fixation; cement penetration; cementing techniques